Assessment of Ground Water Quality at Mawlana Bhashani Science and Technology University Campus, Tangail, Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
An investigation was carried out to determine the pH, EC, TDS, As, Mn, Fe, and Pb in the ground water at Mawlana Bhashani Science and Technology University Campus. The water samples were collected from the tube well and reserved tank at 6 different locations in February, 2012 and August, 2012 covering hall and academic establishment. The concentration of pH, EC, TDS, As, Mn, Fe, and Pb varied 6.4-6.8, 377.5-590?scm-1, 192.5-282ppm, 0.00018-0.0159ppm, 0.07-3.825ppm, 0.00-5. 618 ppm and 0.00- 0.00006 ppm respectively. According to the standard of drinking water pH, EC, TDS, As, and Pb toxicity were not detected and in some cases the concentrations of Mn and Fe were considered as toxicants due to their higher concentrations. Correlation and seasonal fluctuation were also considered in this study. The dry season sample contained higher amount of trace metals than that of wet season.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22114 J. Environ. Sci. & Natural Resources, 6(2): 177-180 2013